Non-invasive preimplantation genetic testing for conventional IVF blastocysts - Pingyuan Xie; Shuoping Zhang; Yifang Gu; Bo Jiang; Liang Hu; Yue-qiu Tan; Yaxin Yao; Yi Tang; Anqi Wan; Sufen Cai; Yangyun Zou; Guangxiu Lu; et al. (Journal of Translational Medicine, 2022)
Abstract Background Previous studies suggested that non-invasive preimplantation genetic testing (niPGT) for intracytoplasmic sperm injection (ICSI) blastocysts can be used to identify chromosomal ploidy and chromosomal abnormalities. Here, we report the feasibility and performance of niPGT for conventional in vitro fertilization (IVF) blastocysts. Methods This was a prospective observational study. In the preclinical stage, whole genome amplification and NGS were performed using the sperm spent culture medium (SCM). Then, trophectoderm (TE) biopsies and corresponding SCM derived from 27 conventional IVF monopronuclear embryos were collected. In the clinical stage, samples from 25 conventional IVF cycles and 37 ICSI cycles from April 2020–August 2021 were collected for performance evaluation. Results Preclinically, we confirmed failed sperm DNA amplification under the current amplification system. Subsequent niPGT from the 27 monopronuclear blastocysts showed 69.2% concordance with PGT results of corresponding TE biopsies. In the clinical stage, no paternal contamination was observed in any of the 161 SCM samples from conventional IVF. While maternal contamination was observed in 29.8% (48/161) SCM samples, only 2.5% (4/161) samples had a contamination ratio ≥ 50%. Compared with that of TE biopsy, the performances of NiPGT from 161 conventional IVF embryos and 122 ICSI embryos were not significantly different (P > 0.05), with ploidy concordance rates of 75% and 74.6% for IVF and ICSI methods, respectively. Finally, evaluation of the euploid probability of embryos with different types of niPGT results showed prediction probabilities of 82.8%, 77.8%, 62.5%, 50.0%, 40.9% and 18.4% for euploidy, sex-chromosome mosaics only, low-level mosaics, multiple abnormal chromosomes, high-level mosaics and aneuploidy, respectively. Conclusions Our research results preliminarily confirm that the niPGT approach using SCM from conventional IVF has comparable performance with ICSI and might broadening the application scope of niPGT.